2007 International Conference on Thermal, Mechanical and Multi-Physics Simulation Experiments in Microelectronics and Micro-Sys 2007
DOI: 10.1109/esime.2007.360010
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Board-level SMT Assembly and Solder Joint Reliability of Different QFN Packages

Abstract: The current paper deals with firstly the optimized SMT to assemble various types of QFN (Quad Flat Nonleaded) packages. The important SMT factors such as solder pad and stencil designs will be discussed. Secondly and more importantly, this paper will detail the comprehensive experiment and simulation work done for QFN solder joint reliability modeling. A curve fitted fatigue correlation model together with the use of Schubert's hyperbolic sine lead-free solder constitutive model will be proposed for accurate Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 3 publications
0
13
0
Order By: Relevance
“…From the accumulated strain energy density per cycle obtained, the characteristic life was calculated using the fatigue life prediction equation established for QFN solder joint [12]. Since the solder joint reliability requirement (2,000 cycles) was the number of cycles to first failure and not the characteristic life of the solder joint, the characteristic life was instead normalized against the baseline model result that showed no failure at 2,000 cycles.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From the accumulated strain energy density per cycle obtained, the characteristic life was calculated using the fatigue life prediction equation established for QFN solder joint [12]. Since the solder joint reliability requirement (2,000 cycles) was the number of cycles to first failure and not the characteristic life of the solder joint, the characteristic life was instead normalized against the baseline model result that showed no failure at 2,000 cycles.…”
Section: Resultsmentioning
confidence: 99%
“…The fatigue correlation above, which is also known as Schubert's correlation model, has been found to have good prediction accuracy for BGA (ball grid array) laminate-based packages but not for leadframe-based packages like QFN (quad flat no lead). Another study [12] showed that a different fatigue correlation model would work well with solder fatigue life prediction for QFNs:…”
Section: Solder Constitutive and Fatigue Lifementioning
confidence: 99%
“…This corner joint was selected for the solder life cycle prediction. The volume-averaging technique presented earlier was implemented to get the accumulated creep strain energy density per cycle for the top solder material interface rom the accumulated strain energy density per cycle obtained, the characteristic life was calculated using the fatigue life prediction equation established for QFN solder joint [3]. But since the requirement (2,000 cycles) was the number of cycles to first failure and not characteristic life of the solder joint, the characteristic life was instead normalized against the baseline model result that showed no failure at 2,000 cycles.…”
Section: Resultsmentioning
confidence: 99%
“…The fatigue correlation above, which is also known as Schubert's correlation model, has been found to have good prediction accuracy for BGA (ball grid array) laminate-based packages but not for leadframe-based packages like QFN (quad flat no lead). Another study [3] showed that a different fatigue correlation model would work well with solder fatigue life prediction for QFNs:…”
Section: Solder Constitutive and Fatigue Lifementioning
confidence: 99%
“…for semiconductors [7] and printed circuit board (PCB) manufacturing and assembly [8,9]. These models are usually limited in scope, developed at specific process steps (e.g.…”
Section: Literature Reviewmentioning
confidence: 99%